International protection of the marine environment from pollution caused by maritime transport - Jasim, Firas Naeem (Al-Adab Journal, 2021)
Research on the topic of pollution of the marine environment by sea transport and its danger to humans, consisting of marine organisms, as its effects are no longer confined to the pollution-exporting country only, and it cannot be described as a regional problem confined to one region without another, but rather it has become a global phenomenon that crosses the political borders of countries that require concerted efforts of all. This necessitated the intervention of the international community to organize the international legal protection of the marine environment from the danger of pollution resulting from maritime transport for this reason, the study of the research necessitated dividing it into two main sections, the first of which dealt with the conceptual framework of the pollution of the marine environment by shipping. While the second dealt with the legal regulation to protect the marine environment from pollution resulting from maritime transport, and then the research ended with a number of conclusions and a set of recommendations that we hope will contribute to strengthening the legal protection of the marine environment from pollution resulting from shipping within the framework of international law.